Acta Medicinae Legalis Et Socialis 2010
DOI: 10.14195/978-989-26-0173-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Paternal and maternal lineages in Cabo Verde archipelago population

Abstract: A navegação consulta e descarregamento dos títulos inseridos nas Bibliotecas Digitais UC Digitalis, UC Pombalina e UC Impactum, pressupõem a aceitação plena e sem reservas dos Termos e Condições de Uso destas Bibliotecas Digitais, disponíveis em https://digitalis.uc.pt/pt-pt/termos.Conforme exposto nos referidos Termos e Condições de Uso, o descarregamento de títulos de acesso restrito requer uma licença válida de autorização devendo o utilizador aceder ao(s) documento(s) a partir de um endereço de IP da insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The close genetic proximity between Palenque and Cabo Verde can be explained by their similar European-dominated colonial history (Portuguese/Spanish slave trade) as well as their similar admixed proportion of European and African contributions. A high male European contribution has been reported earlier in samples from Cabo Verde (Carvalho et al, 2010;Gonçalves et al, 2003), and the same high European male contribution was also found in our sample from Palenque. The remaining samples in the plot are consistent with a higher percentage of chromosomes with European rather than African or Native American origin.…”
Section: Genetic Distance Between the Populations Of Bolivar And Thossupporting
confidence: 92%
“…The close genetic proximity between Palenque and Cabo Verde can be explained by their similar European-dominated colonial history (Portuguese/Spanish slave trade) as well as their similar admixed proportion of European and African contributions. A high male European contribution has been reported earlier in samples from Cabo Verde (Carvalho et al, 2010;Gonçalves et al, 2003), and the same high European male contribution was also found in our sample from Palenque. The remaining samples in the plot are consistent with a higher percentage of chromosomes with European rather than African or Native American origin.…”
Section: Genetic Distance Between the Populations Of Bolivar And Thossupporting
confidence: 92%